Thrombocytopenia due to monsoon related illness: as an underestimated cause of maternal mortality and morbidity - Kharat, Pallavi Amol; Borkar, Shital; Dalvi, Naina (International Journal of Research in Medical Sciences, 2020)
Background: Thrombocytopenia is a second leading cause of blood disorder in pregnancy after anaemia. It is defined as platelet count below 1,50,000/ul. It is a common condition occurring in approximately 7-10% of pregnancies. Gestational thrombocytopenia is physiological and occurs in 70-80% of population having platelet count of 1,30,000/ul-1,50,000/ul with no adverse consequences. Other causes of thrombocytopenia in pregnancy could be immune related like immune thrombocytopenia, thrombotic thrombocytopenia or pregnancy related disorders like hypertensive disorders, eclampsia, HELLP and fatty liver of pregnancy. Besides this, pregnant ladies can have thrombocytopenia associated with fever which is commonly observed in monsoon season. It could be because of various causes like dengue, malaria, leptospirosis or other viral infections. Thrombocytopenia carries a risk of haemorrhage for both mother as well as newborn. It carries a risk of vertical transmission leading to premature birth, neonatal thrombocytopenia, intracranial haemorrhage and foetal death. There is relatively less information regarding importance of diversity of infectious diseases on pregnancy outcome. Methods: 14 pregnant patients were studied on the basis of their history of fever, platelet count below 1,50,000/ul and any history of haemorrhage or petechie during monsoon period from June to September 2019 admitted in gynaecological ward in HBTMC and Dr. R. N. Cooper Hospital, Mumbai. All patients were subjected to fever profile, repeated haemogram for platelet trend and medical reference was done. Results: Out of 14 patients, 9 patients had negative fever profile, 2 were dengue positive, 2 were widal positive and one was leptospira positive patient. All patients had platelet count less than 1,50,000/ul out of which 3 patients received platelet transfusion.. Conclusions: Monsoon fever with thrombocytopenia requires early diagnosis and optimal treatment to reduce maternal mortality and to avoid adverse fetal outcome. There is a strong need to create awareness amongst the community.